2014
DOI: 10.1111/1750-3841.12392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Fate of Escherichia coli O157:H7 and Salmonella enterica in the Agricultural Environment: Current Perspective

Abstract: The significance of fresh vegetable consumption on human nutrition and health is well recognized. Human infections with Escherichia coli O157:H7 and Salmonella enterica linked to fresh vegetable consumption have become a serious public health problem inflicting a heavy economic burden. The use of contaminated livestock wastes such as manure and manure slurry in crop production is believed to be one of the principal routes of fresh vegetable contamination with E. coli O157:H7 and S. enterica at preharvest stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Weekly farm management practices and environmental parameters were not tracked in detail over the entire period of this current study. However, a more cohesive collection of these parameters, as well as projects conducted throughout different seasons, might illuminate other associations related to the peaks of generic E. coli MPN/g in the soil, as suggested by various authors (Fraser et al, 2013;Gorski et al, 2011;Ongeng et al, 2014;Reed-Jones et al, 2016;Salaheen et al, 2015). Warmer temperatures and precipitation occurring in the spring and summer have been shown in past studies to be correlated with increased incidence and survival of foodborne pathogens in the environment (Fraser et al, 2013;Gorski et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Weekly farm management practices and environmental parameters were not tracked in detail over the entire period of this current study. However, a more cohesive collection of these parameters, as well as projects conducted throughout different seasons, might illuminate other associations related to the peaks of generic E. coli MPN/g in the soil, as suggested by various authors (Fraser et al, 2013;Gorski et al, 2011;Ongeng et al, 2014;Reed-Jones et al, 2016;Salaheen et al, 2015). Warmer temperatures and precipitation occurring in the spring and summer have been shown in past studies to be correlated with increased incidence and survival of foodborne pathogens in the environment (Fraser et al, 2013;Gorski et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…STEC is usually introduced into agricultural environments by livestock and/or wildlife faeces (Jay-Russell, 2013;Reed-Jones, Marine, Everts, & Micallef, 2016). Sheep are asymptomatic reservoirs of STEC and faecal shedding from ruminants may increase during periods of stress (Cooley et al, 2013;Edrington et al, 2009;Moynihan, Richards, Ritz, Tyrrel, & Brennan, 2013;Ongeng et al, 2014;Schilling et al, 2012). Raw manure deposited in production fields by grazing animals may introduce enteric foodborne pathogens into the growing environment and lead to increased contamination of produce, especially those high-risk crops that grow in contact with the soil, which then may become vehicles for these pathogens in the food supply (Gorski et al, 2011;Hoar et al, 2013;Niemira & Zhang, 2014;Salaheen et al, 2015;Strawn, Fortes, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is reasonable body of evidence suggesting that Salmonella enterica adapts to different environments such as manure or soil (Semenov et al, 2010;Fornefeld et al, 2017). The fate of Escherichia coli and Salmonella in soil and soil-related environments was investigated in several studies (Ongeng et al, 2014;Mallon et al, 2015;Fornefeld et al, 2017;Wang et al, 2018). Furthermore, a number of studies have shown that the survival and success of an invader in a new (soil) environment depends on various biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Each year, Salmonella enterica is responsible for 12 to 33 million human typhoid cases (2) and 1.3 billion cases of gastroenteritis worldwide (3), with approximately 3.5 million deaths. It is frequently the leading cause of foodborne infections in the United States annually (4) and a persistent agricultural problem, as Salmonella strains infect livestock (5); this in turn exposes humans to contaminated food sources (6). S. enterica subsp.…”
Section: Introductionmentioning
confidence: 99%